1998
DOI: 10.1258/0956462981922548
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between history of contact with people living with HIV AIDS PWAs and tolerant attitudes toward HIV AIDS and PWAs in rural Thailand

Abstract: This study examines the hypothesis that people who have more contact with PWAs (people living with AIDS) are more tolerant than those who have no contact with them. Four provinces with different incidence of AIDS in 4 different regions of Thailand were selected. Structured questionnaire interviews were conducted with village people, asking about their history of contact with PWAs, and knowledge and attitudes toward HIV/AIDS and PWAs (n = 434). An 'Attitude Score', which indicates an accepting attitude (or tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Consistent with the results of different studies [17,18], respondents who were acquainted with PLWHA were more likely than others to be less discriminatory toward PLWHA. The prevalence of HIV in Hong Kong is, however, low [40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the results of different studies [17,18], respondents who were acquainted with PLWHA were more likely than others to be less discriminatory toward PLWHA. The prevalence of HIV in Hong Kong is, however, low [40].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have identified that some background and social factors such as gender [4,13], age [4,[13][14][15], education level [4,13,15,16] and experience of personal interaction with PMI or PLWHA [17][18][19][20] were associated with discriminatory attitudes toward PMI or PLWHA, though mixed findings have been reported [21][22][23][24]. Nevertheless, there may be attitudinal factors that are only relevant to discrimination against PLWHA.…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, Pitts and Jackson (1993) found personal portrayals to be the most powerful vehicles for AIDS information. Takai et al (1998) conducted the first analytical study in Thailand to examine influences on people's attitudes to AIDS. Contact with PWHA resulted in significantly more tolerant attitudes towards HIV and PWHA because, the authors argue, people are forced to think of the issues as their own.…”
Section: The Effect Of Meeting a Person Living With Hivmentioning
confidence: 99%
“…2 Further, in Thailand it was found that those with histories of contact with people living with HIV/AIDS were more tolerant of the disease in general as well as of those infected. 3 However, community benefits such as the reduced incidence of HIV infection and reductions in stigma and discrimination cannot be realized without disclosure by HIVpositive individuals.…”
mentioning
confidence: 99%